2010
DOI: 10.1210/en.2009-1483
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Gonadotropin-Releasing Hormone-Induced Extracellular Signal-Regulated Kinase Activation by Dual-Specificity Protein Phosphatase 1 in LβT2 Gonadotropes

Abstract: As the regulator of pituitary reproductive hormone synthesis, the hypothalamic neuropeptide GnRH is the central regulator of reproduction. A hallmark of GnRH action is the differential control of gene expression in pituitary gonadotropes through varied pulsatile stimulation. Among other signaling events, GnRH activation of the ERK family of MAPKs plays a significant role in the transcriptional regulation of the luteinizing hormone β-subunit gene and regulation of cap-dependent translation. We evaluated the ERK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 48 publications
2
22
0
Order By: Relevance
“…The mechanisms of ROS action are not well defined, but primary targets of H 2 O 2 are protein tyrosine and dual specificity phosphatases bearing active site cysteine residues that are inactivated by oxidation (69). It is possible that ROS directly participate in regulation of activity through modulation of tyrosine and dual specificity kinases, which control overall MAP kinase and tyrosine kinase activity and are known participants in MAP kinase regulation by GnRH (35,70). The impact of ROS on expression of Atf3, c-Fos, Jun, and Egr1 mRNA, and on promoter activation and mRNA level of both Fshb and Lhb suggests that ROS participates in the major regulatory mechanisms engaged by GnRH in gonadotropes The participation of ROS in the GnRH signaling network is of general significance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanisms of ROS action are not well defined, but primary targets of H 2 O 2 are protein tyrosine and dual specificity phosphatases bearing active site cysteine residues that are inactivated by oxidation (69). It is possible that ROS directly participate in regulation of activity through modulation of tyrosine and dual specificity kinases, which control overall MAP kinase and tyrosine kinase activity and are known participants in MAP kinase regulation by GnRH (35,70). The impact of ROS on expression of Atf3, c-Fos, Jun, and Egr1 mRNA, and on promoter activation and mRNA level of both Fshb and Lhb suggests that ROS participates in the major regulatory mechanisms engaged by GnRH in gonadotropes The participation of ROS in the GnRH signaling network is of general significance.…”
Section: Discussionmentioning
confidence: 99%
“…The cells were plated a density of 2.75 ϫ 10 5 cells/cm 2 and incubated for 24 hours before transfection. Reporter genes were cotransfected with a pGL3-basic reporter plasmid containing the herpesvirus thymidine kinase promoter and a substitution of the luciferase coding sequence with ␤-galactosidase, pGL3-TK-Gal, to serve as an internal control (34,35). Transfected cells were preincubated with 5 M DPI or 10 mM N-acetyl cysteine (NAC) for 30 minutes and then incubated with 10 nM GnRH (Sigma-Aldrich, St Louis, MO) for 5 hours.…”
Section: Transfection and Luciferase Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Kanasaki et al initially observed that slow GnRH pulses triggered a more rapid and sustained phosphorylation of ERK1/2 than fast pulses (8). Subsequently, the feedback activity of MKP1, which inactivates MAPK via dephosphorylation, was found to modulate GnRH-induced ERK activation and gonadotropin response to GnRH (34,35). Finally, MKP1 expression was shown to be predominant under high GnRH frequency compared with low GnRH frequency (36).…”
Section: Discussionmentioning
confidence: 99%
“…DUSP1 is constitutively expressed in LβT2 cells, and mRNA and protein levels are increased in response to GNRH stimulation. DUSP1 protein modulates ERK activation in LβT2 cells and affects Lhb promoter activity (Nguyen et al, 2010). The Dusp1 mRNA contains a 3’ UTR ARE which binds HuR, causing improved stabilization and translation (Kuwano et al, 2008).…”
Section: Post-transcriptional Control Of Gene Expressionmentioning
confidence: 99%